Prediksi Tutupan Lahan dalam Melihat Perkembangan Lahan Sawah di Kota Gorontalo Menggunakan Permodelan Cellular Automata - Muhammad Ghozali Pulukadang; Bitta Pigawati (Jurusan Perencanaan Wilayah dan Kota, 2023)
Land development in Indonesia currently tends to have a significant impact on land use change. Gorontalo City is one of the provincial capitals which currently still has an area of more than 800 ha of rice fields. The growing issue related to rice fields is that 50% of the currently identified rice fields will become built up land because they have accessibility and facilities that support the development of built up land. The purpose of this study is to predict the development of land cover in the City of Gorontalo and to analyze the conversion of paddy fields into built-up land. Rice fields are productive lands that are quite important in Gorontalo City, so it is necessary to know how much the reduction is due to the development of built-up land. The dynamics of land cover changes spatially will be analyzed using the Cellular Automata (CA) model with a period of 10 years. The results obtained from this study indicate that the prediction of land cover development with a validation value of 0.55 (Accuracy of Moderate), especially built-up land in 2030 increases by 592 Ha and the conversion of paddy fields into built-up land in 2030 covers an area of 300 Ha in the District North City. The results of this study can be used as recommendations and considerations for Gorontalo City government policies in controlling land in order to achieve a sustainable city.